2013
DOI: 10.5296/ijld.v3i3.4068
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Distance Learners’ Attrition Rate at the University of Cape Coast: Tutors’/Students’ Perception

Abstract: The goal of Distance Education in Ghana is to make quality education, especially at the tertiary level, more accessible and relevant to meeting the human resource needs of the country. This is to improve performance as well as the quality of lives of Ghanaians. This dream can only be realised if students enrolled on the programmes graduate on schedule. Students' enrollment on the Distance Education Programme at the University of Cape Coast (UCC) currently is over 24,000. However, not every student enrolls on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(7 reference statements)
2
2
0
Order By: Relevance
“…The researcher strongly believes that if these problems remain unsolved, this might in turn lead to dropping out. In terms of feelings of isolation, this finding is in accord with the studies conducted by Boateng and Boadu (2013) and Yang et al (2013) indicating that connectedness is a central issue in distance and e-learning context.…”
Section: Other Possible Reasons For Dropping Outsupporting
confidence: 90%
See 2 more Smart Citations
“…The researcher strongly believes that if these problems remain unsolved, this might in turn lead to dropping out. In terms of feelings of isolation, this finding is in accord with the studies conducted by Boateng and Boadu (2013) and Yang et al (2013) indicating that connectedness is a central issue in distance and e-learning context.…”
Section: Other Possible Reasons For Dropping Outsupporting
confidence: 90%
“…The findings of the current study showed that at Stage 1, despite being able to resit examinations, a student decided to exit from the Programme of Study because of failure to pass the examination. The finding seems to be consistent with Boateng and Boadu (2013) and Rashid et al (2015) who low academic capability is a reason to consider signing off on the program.…”
Section: Lack Of Basic Skills Of Englishsupporting
confidence: 74%
See 1 more Smart Citation
“…Several studies had been conducted to investigate measures that can enhance students' retention at the college. Studies that have investigated this phenomenon include that of Arhin and Wang'eri (2018) and Akuamoah-Boateng and Boadu (2013). Although the College has made tremendous efforts to put in place some measures based on the recommendations of the studies, retaining students at the college is still a problem.…”
Section: Introductionmentioning
confidence: 99%